Numerical Modeling of Wires Incorporation Response Applied To a Concealed Cable (International Journal of Sustainable Energy and Environmental Research, 2014)
In recent years hoisting ropes have been increasingly used for construction of complex structures: tall buildings, bridges and far-reaching platform for oil drilling, nuclear plants, etc. These structures have complex geometry and subjected to environmental loads, and operation which can cause to material many conditions beyond its elastic limit, and created a need to better understand of metal-based cables behavior. For these situations, conventional methods of calculation or those given the current regulations are not sufficient to give a reliable representation of load-displacement relationship, state of deterioration, resistance and failure mode of structures. The quantification of these phenomena aims to design and build those equipments in safe, economic, sustainable methods and must be made by means of numerical methods, including the finite element one. Although it is possible to establish a model without considering the effects which can allow a microscopic level, however, they are many determinants of mechanical response of cable factors. That is why their knowledge will be of great interest for modeling the behavior of materials. We therefore mention mechanical behavior of cables with the fundamental relation of damage which will be used for modeling the stress-strain relationship. The present work falls within this context, our goal is to develop a behavior model for the lifting cables, designed for the calculation of structures by numerical methods in trying to incorporate most of the factors with their non- response linear behavior.